2017
DOI: 10.1089/brain.2017.0525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Field Spread on Resting-State Magneto Encephalography Functional Network Analysis: A Computational Modeling Study

Abstract: A popular way to analyze resting-state electroencephalography (EEG) and magneto encephalography (MEG) data is to treat them as a functional network in which sensors are identified with nodes and the interaction between channel time series and the network connections. Although conceptually appealing, the network-theoretical approach to sensor-level EEG and MEG data is challenged by the fact that EEG and MEG time series are mixtures of source activity. It is, therefore, of interest to assess the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…However, the accuracy of these methods in conjunction with graphical network analysis is not yet established, and the good approximation of planar gradiometer topography to underlying cortical sources provides sufficient resolution to test our current hypotheses. Simulation studies confirm that multivariate auto-regression modelling is more robust in sensor space ( Michalareas et al , 2013 ), while the use of lagged interaction measures from planar gradiometer data are less sensitive to field-spread ( Pereira et al , 2017 ). Our own simulations provided further evidence that the analysis of sensor space graph metrics accords with source space generators of the data.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the accuracy of these methods in conjunction with graphical network analysis is not yet established, and the good approximation of planar gradiometer topography to underlying cortical sources provides sufficient resolution to test our current hypotheses. Simulation studies confirm that multivariate auto-regression modelling is more robust in sensor space ( Michalareas et al , 2013 ), while the use of lagged interaction measures from planar gradiometer data are less sensitive to field-spread ( Pereira et al , 2017 ). Our own simulations provided further evidence that the analysis of sensor space graph metrics accords with source space generators of the data.…”
Section: Discussionmentioning
confidence: 91%
“…An advantage of this method for MEG/EEG is that it is less sensitive to the field spread that otherwise inflates instantaneous correlation metrics ( Baccalá and Sameshima, 2001 ; van Dellen et al , 2013 ; Colclough et al , 2016 ). When combined with the focal field-of-view of planar gradiometers, simulation studies confirm that multivariate autoregressive modelling minimizes field spread while remaining veridical to source–space interactions ( Pereira et al , 2017 ). Indeed, our own simulations confirmed that this approach can recover average local efficiency of source-level networks, provided signal-to-noise ratio is sufficiently high ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The interfering factors to be considered in MEG data analysis are field spread (FS) and volume conduction (VC). Because of the topographical representation of magnetic field beyond the source, signal can be picked up at some distance and it is termed as field spread (Silva Pereira et al, 2017 ). Due to FS, a signal from one underlying source can be present in multiple time series.…”
Section: Meg Data Analysismentioning
confidence: 99%
“…is computed for nodes i and j, where < • > denotes averaging over time [45]. One may note that the PLI takes values between 0 (random phase relations or perfect synchrony) and 1 (perfect phase locking).…”
Section: Spontaneous Activitymentioning
confidence: 99%